Visible-light-enabled regioselective aerobic oxidative C(sp2)-H thiocyanation of aromatic compounds by Eosin-Y photocatalyst. Issue 50 (10th December 2020) - Yi, Bing; Wen, Xiaoyong; Yi, Ziqi; Xie, Yanjun; Wang, Qiang; Tan, Jian-Ping
Graphical abstract: Highlights: Visible-light-enabled regioselective C(sp 2 )-H thiocyanation. Eosin-Y as photocatalyst and oxygen as the green oxidant. Green, efficient and operationally simple. Broad substrate scopes and gram scale synthesis. Abstract: Herein, visible-light-enabled regioselective aerobic oxidative C(sp 2 )-H thiocyanation of aromatic compounds has been developed by employing eosin-Y as effective photocatalyst and oxygen as the green terminal oxidant. This process featured green, efficient and operationally simple. Furthermore, the practicality and utility of this protocol was demonstrated by the gram scale synthesis. Mechanistic studies suggested that this reaction was realized via a photoredox radical pathway.